Analisis AC-WC Dengan Campuran Bahan Tambah Shell Waste Dan Waste Glass Sebagai Additive Untuk Perkerasan Jalan - Nur Rahman; Singgih Aji Saputra; Rachmat Mudiyono (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study evaluates the performance of Asphalt Concrete-Wearing Course (AC-WC) mixtures incorporating shell waste and waste glass as additives for sustainable pavement applications. The optimum asphalt content was determined at 5.8% using the Marshall method, producing balanced volumetric and mechanical properties that satisfy heavy traffic specifications. Waste glass addition without shell waste increased mixture stiffness but did not consistently achieve optimal stability due to volumetric imbalance. A synergistic effect was observed when shell waste and waste glass were combined. The mixture containing 5% shell waste and 5% waste glass demonstrated the most favorable performance, characterized by higher stability, proportional Marshall Quotient, controlled air void distribution, and improved structural integrity. Increasing shell waste content to 7.5% and 10% did not enhance performance and tended to reduce volumetric balance. Economic evaluation indicates a material cost reduction of approximately 1.72% per kilometer compared to conventional mixtures, without compromising mechanical performance. The findings confirm that the optimal incorporation of shell waste and waste glass is technically feasible and economically beneficial for sustainable AC-WC pavement construction.